MARKEDNESS AND INTERLANGUAGE DEVELOPMENT IN SPEAKING : AN ANALYSIS OF ENGLISH DEPARTMENT STUDENTS’ SPOKEN LANGUAGE OF STKIP PGRI SUMATERA BARAT - yelfiza, yelfiza (Jurnal Curricula, 2016)
Abstract     This article is proposed to find out the development of interlanguage, especially the variability of the system the students use in speaking caused by linguistic markedness. Data were collected from participants when they performed their speech. The speech was recorded so that the writer can replay it after the research.     The participants were chosen from those who were conssidered better students for the sake of practicality in collecting the data. The writer analyzed 3 speeches spoken by three participants. To study interlanguage development of the poor students is quite difficult, because they produce the language without the knowlege of English. Therefore, there is no fixed system found when they produce English.Having collected the data and analyzed them, the writer found that interlanguage development is influenced by markedness. Markedness can be divided into marked and unmarked and it is one of the sources of difficulty. The students construct their own system of English based on the markedness they can identify. If they cannot see or listen to the markedness, they tend to make overgeneralization.